Association between frequency of pain in the oral cavity and time elapsed since the last dental - Pietrapiana León y León, Francesco (2021)
Objective: To determine the association between frequency of pain in the oral cavity and time elapsed since the last dental visit based on data collected from The National Health and Nutrition Examination Survey (NHANES) in a United States’ population. Materials and Methods: The study was observational, retrospective, transversal and analytical. Data was obtained from NHANES 2017-2018 questionnaire and database. Population, once adapted to the study’s selection criteria was of 3696. Uni-variable analysis was conducted through absolute and relative frequencies, bi-variable, compared the principal variables through Chi Squared and multi-variable associated this two with the rest through Poisson’s regression. Association by prevalence ratios was reported and 95% confidence intervals were included. Results: When participants chose “often” or “very often” in pain frequency, a positive association was shown while only using the dependent and independent variables (PR=1.27 C.I. = 0.97 a 1.66). When compared, analysis showed that people who waited more than a year, sought dental attention because of pain. Once all categories were added to the regression, prevalence ratios are higher (PR=1.43 C.I 1.11 a 1.84). Conclusions: Results show association between frequency of pain in the oral cavity, time elapsed since the last dental visit and the other categories, hence, strategies to reduce this period of time must be proposed.